Effect of Polymer Binder on the Transparent Conducting Electrodes on Stretchable Film Fabricated by Screen Printing of Silver Paste. (23rd October 2017) - Lim, Chan Kyu; Lee, Yo Seb; Choa, Sung Hoon; Lee, Deuk Young; Park, Lee Soon; Nam, Su Yong
Abstract : Smart wearable devices and sensors have been fabricated by screen printing of metal paste as functional circuits since the metal interconnects exhibited much less electrical resistance than other conducting materials such as carbon nanotube or conducting polymers (PEDOT:PSS). In this study, we chose silver particle as conductive material in the form of silver paste and used screen printing to fabricate a stretchable touch screen panel utilizing metal mesh method for the transparent electrode patterning. The rheological study of Ag pastes showed that the binder polymer with high molecular weight and low glass transition temperature (T g ) can stabilize the Ag paste with Ag particle content over 80% by weight. The stretching and bending tests of Ag electrode films obtained by screen printing indicated that good conductivity of Ag electrodes is related to the stability of Ag paste obtained with the high molecular weight binder polymer.